Capaian Tugas Perkembangan Sosial Siswa dengan Kelompok Teman Sebaya dan Implikasinya terhadap Program Pelayanan Bimbingan dan Konseling - Ardi, Zadrian; Ibrahim, Yulidar; Said, Asrul (Konselor, 2012)
The purpose of this research is to describe: 1) level of adolescence’s ability in a more mature relationship with peers, 2) level of adolescence’s ability in performing sections of youth social roles according to gender, 3) Implications for social development task with the guidance and counseling program. Research methods used are descriptive analysis. Population research derived from class XI SMA Negeri 1 Padang. Sample of research taken by using Proportional Random Sampling. Research findings of adolescence’s ability in a more mature relationship with peers and level of adolescence’s ability in performing sections of youth social roles according to gender in general terms has been reached. Some indicators of research instrument that still has a low reached made in the preparation of guidance and counseling program.